REPRODUCTION BIOLOGY OF TRUE PERCULA CLOWN FISH Amphiprion percula IN HATCHERY - Ketut Maha Setiawati; Gunawan Gunawan; Jhon Harianto Hutapea (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
True percula clown fish (Amphiprion percula) is one of marine ornamental fish with high economic value and can spawn throughout the year in an aquarium. The aims of this research were to understand reproduction aspects of true percula clown fish broodstock in an aquarium. A pair of broodstock used in this experiment were 4-9 cm in total length and maintained in an aquarium of 60x40x30 cm3 dimension. Numbers of brrodstock were 18 pairs and each aquarium filled with one pair of broodstock. During the experiment, fish were fed with artificial feed first and one hour later with mysids shrimp and copepod until satiation twice a day. Parameters observed were broodstock size, numbers and hatching rate of eggs. The results showed, the size of spawned female were range from 6.6-9.5 cm and male from 4.6-6.2 cm. Average of eggs produced per spawning was varied 423±255 with the average of spawning frequency was 2.78±0.38 times/month. Broodstock was spawn partially with the maximum spawning frequency of single broodstock was 4 times/month. The biggest female with size of 9.5 cm was still productive and spawn 3 times/month. There was a pair of broodstock which can produce more than 700 eggs/spawning. This results indicated that true percula clown fish can spawn throughout the year in the aquarium with varied of eggs number and spawning frequency for each individual and spawning period. The average of hatching rate during the experiment was 79.72±13.73 % with range between first to the next spawning 0f 7-14 day.Keywords: reproduction, true percula clown fish, Amphiprion percula, hatching rate